Performance Analysis of IPv4 and IPv6 in Network Traffic Management Using Various Queuing Mechanism Algorithms - Harly, Sukry (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
Internet Protocol Address (IP Address) is a crucial element in computer networks that enables communication between devices. As the demand for IP addresses increases, the transition from IPv4 to IPv6 becomes increasingly important. This research analyzes the performance of IPv4 and IPv6 in network traffic management using various queuing mechanism algorithms, such as FIFO, WFQ, PQ, and CBWFQ. The Network Development Life Cycle (NDLC) approach is used to test bandwidth, latency, and packet loss parameters in IPv4 and IPv6-based network scenarios. The results show that IPv4 has higher bandwidth, while IPv6 offers better network stability. The CBWFQ queuing mechanism proved effective in managing data traffic and ensuring quality of service. This study provides recommendations for network managers to choose suitable queuing protocols and algorithms to improve network efficiency.